Refining the Indonesian Geoid Model: A Comparative Study of Global Geopotential Models in East Kalimantan - Fahri Dean Alvito; Zulfikar Adlan Nadzir; Misfallah Nurhayati (Departemen Teknik Geomatika ITS, 2025)
Gravity field along with its derivative, geoid, is one of the important pillars of Geodesy. The geoid is utilized in many countries as the vertical reference system, Indonesia as well. However, Indonesia is unique in topography, made the computation of geoid model throughout the archipelago a challenge. The development of geoid model in Indonesia has 4 phases, with the latest in 2020 and 2023. INAGEOID2020 is the Indonesian geoid model used as vertical reference frame for vertical control in Indonesia, updated to version 2.0 in 2023. However, it has not achieved the target accuracy of 5 cm throughout the country. INAGEOID2020 v2.0 is based on the EGM2008 global geopotential model (GGM) with order and degree 360, which is now nearly 20 years old. The implementation of EGM2008 into the regional model also lacked a fitting process, relying solely on functional calculations. This study proposes using modern GGMs, namely EGM2008, XGM2019e, and SGG-UGM-2, along with a fitting process to improve geoid modeling, to optimize the future iteration of Indonesian Geoid Model. The research compares the gravimetric undulations of these models to geometric undulations at 264 validation points, both with and without fitting in East Kalimantan. The fitting improved the accuracy of EGM2008 and XGM2019e, but SGG-UGM-2 performed worse due to elevation discrepancies both before and after the fitting, mainly due to difference on the starting point close to the coast. XGM2019e at degree 2190, truncated to 720 and 360 showed the best results after the fitting, achieving standard deviation and root mean square error (RMSE) values of 0.061 m and 0.064 m, respectively. The performance of EGM2008 is not far behind XGM2019e. This finding indicates that the XGM2019e is the best out the trio, making it a promising alternative to be utilized for future geoid modeling in Indonesia.